Diversity, distribution and conservation status of island conifers: a global review. Issue 3 (16th December 2013) - Rumeu, Beatriz; Afonso, Virginia; Fernández‐Palacios, José María; Nogales, Manuel; Rejmanek, Marcel
Abstract Aim Conifers comprise an ancient and diverse group of plants showing a wide distribution range. To better understand the general patterns of species successfully established on islands, this review compiles information about the distribution, diversity, dispersal potential and conservation status of insular conifers, with special emphasis on those inhabiting remote oceanic islands. Location Global. Methods An exhaustive survey was made of world‐wide databases and literature. We registered information on island distribution (including ocean region, extension and geological origin of the island), endemism and threat status for each insular conifer. Results 285 of the 547 conifer species considered in this review show an insular distribution (i.e. their distribution encompass insular territories). The family Podocarpaceae is best represented, with 40% of the insular species. The importance of endozoochory for long‐distance dispersal is clear, because it was the most frequent dispersal syndrome among oceanic conifers. A high proportion of the total threatened conifers occur on islands (52%), and many of them are insular endemics (72%). Among conifer families, Araucariaceae is the most threatened in insular territories. Main conclusions Our results highlight the wide diversity of insular conifers, as well as the key role of oceanic islands in catalysing speciation mechanisms. Pacific islands in particular harbour the greatest diversity levels, constituting a major centre of diversification. The wide distribution of conifers reflects their great potential for dispersal and colonization, endozoochory being the most favourable dispersal syndrome for reaching remote islands. The general threat status of insular conifers highlights the fragility of island biota and the urgent need for policies focused on their preservation.